2016
DOI: 10.5344/ajev.2016.15083
|View full text |Cite
|
Sign up to set email alerts
|

Preveraison Water Deficit Accelerates Berry Color Change in Merlot Grapevines

Abstract: Abstract:In red varieties, berry color change from green to red is one of the first events associated with ripening and is often used as an indicator of veraison by viticulturists. Water deficit can accelerate ripening and increase pigment accumulation in the berry skin. The impact of water deficit on the timing and progression of berry color change in the vineyard has been largely overlooked. Here we present three years of observations (2011 to 2013) on the progression of color change in Merlot vines subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In 2017, average preveraison Ψ stem ≈ -0.68 MPa across treatments, yet foliar symptoms were first observed approximately two weeks preveraison (25 July); while in 2018, average preveraison Ψ stem ≈ -1.12 MPa across treatments, and symptoms were observed approximately at veraison (5 August). Since the appearance of foliar symptoms of GRBD are dependent on vine phenology ( Blanco-Ulate et al, 2017 ), and preveraison water deficits have been shown to accelerate coloration of berries at veraison ( Castellarin et al, 2007 ; Herrera and Castellarin, 2016 ), this result suggests that the onset of foliar symptoms is dependent on factors other than water status such as carbohydrate/nutrient status and/or solar radiation. Although vine nutrient status was not monitored in this study, it should be noted that 2018 was characterized by wildfire smoke that significantly reduced solar radiation during the preveraison period that could have delayed the onset of symptoms in that year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, average preveraison Ψ stem ≈ -0.68 MPa across treatments, yet foliar symptoms were first observed approximately two weeks preveraison (25 July); while in 2018, average preveraison Ψ stem ≈ -1.12 MPa across treatments, and symptoms were observed approximately at veraison (5 August). Since the appearance of foliar symptoms of GRBD are dependent on vine phenology ( Blanco-Ulate et al, 2017 ), and preveraison water deficits have been shown to accelerate coloration of berries at veraison ( Castellarin et al, 2007 ; Herrera and Castellarin, 2016 ), this result suggests that the onset of foliar symptoms is dependent on factors other than water status such as carbohydrate/nutrient status and/or solar radiation. Although vine nutrient status was not monitored in this study, it should be noted that 2018 was characterized by wildfire smoke that significantly reduced solar radiation during the preveraison period that could have delayed the onset of symptoms in that year.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation management is arguably the most effective tool for controlling all aspects of vine growth and development ( Williams and Matthews, 1990 ). While moderate water deficits can advance ripening and improve fruit quality ( Matthews and Anderson, 1988 ; Castellarin et al, 2007 ; Herrera and Castellarin, 2016 ), severe water deficits can reduce vegetative growth, photosynthesis, and yield ( Williams et al, 2010a ; Williams et al, 2010b ; Williams, 2012 ). The onset of ripening in grape involves a transition from xylem to phloem water transport into berries ( Greenspan et al, 1994 ), thus the advancement of ripening due to water deficits may also interact with present GRBV infection given its putative limitation to the phloem ( Sudarshana et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of multiple stress regulons ( Nakashima et al, 2014 ) might be critical to orchestrate the balance between stress-responsive regulation and the berry ripening program. These examples suggest that increased osmotic stress signals induced by water deficit may further fine-tune the ripening program through regulating multiple interacting TFs, possibly accelerating ripening ( Castellarin et al, 2007b ; Herrera and Castellarin, 2016 ). Further supporting this, several TF ‘switch’ genes that may be master regulators of berry ripening, such as VviMYBA1-2 , VviNAC1/VviNAC33-47-71 , and VviLBD15-18-38 ( Palumbo et al, 2014 ), are induced under water deficit from the onset of ripening onward.…”
Section: Discussionmentioning
confidence: 99%
“…RDI during ripening has shown promising results, enhancing red skin color in several wine and table grape cultivars [22,24,31,32]. In fact, previous results in experiments carried out by us on "Crimson Seedless" (a midseason cultivar) in the same location showed earlier and more intense acquisition of red color in the skin of the berries leading to higher commercial yield, without negative effects on berry size or production [23].…”
Section: Discussionmentioning
confidence: 99%
“…As stated before, better results were obtained by our team on "Crimson Seedless" (with longer periods of RDI). Several authors have also documented color improvement in wine and table grape cultivars in response to DI [22,24,31,33].…”
Section: Discussionmentioning
confidence: 99%